A scoping review of effects of acute exercise on executive function: evidence from event-related potentials - Cai, Zhidong; Shi, Lin; Wu, Wenjie; Meng, Liang; Ru, Yao; Wu, Moulin (Frontiers in Psychology, 2025)
BackgroundAlthough the acute effects of exercise on executive function are extensively documented in the field of exercise psychology, a thorough assessment of neuroelectric brain activity that is underlying executive function following acute exercise is absent. This systematic review investigated the effects of acute exercise on event-related potentials through their amplitude and latency.MethodsSix electronic databases were searched from their inception to April 15, 2024. This review analyzed the influence of variables such as exercise dosage, test duration, population characteristics, and physical fitness on event-related potential components and executive function. The proportions of positive and null or negative effects across all studies were systematically assessed.ResultsIn total, 52 studies were included in the analysis. The results revealed that 45 (86.5%) of the 52 studies focused on inhibitory control, with moderate-intensity aerobic exercise lasting 16–35 min demonstrating a positive effect on event-related potential components. Nine event-related potential components were examined, with P3 (observed in 43 studies), N2 (17 studies), and N1 (5 studies) being the most frequently reported. Thirty-seven studies (86%) demonstrated that exercise enhanced P3 wave amplitude, whereas 13 studies (27.1%) observed a reduction in latency. Eight studies (53.3%) indicated an increase in N2 wave amplitude following exercise, whereas two studies (13.3%) reported a decrease in latency.ConclusionModerate-intensity acute aerobic exercise lasting 16–35 min demonstrates a positive impact on both executive function performance and event-related potential components, with effects lasting approximately 30 min. The optimal intervention dosage for resistance exercise, mind–body exercise, and other types of exercise necessitates further investigation in future studies.